Growth and production of cocoons of Eisenia foetida (redworm) on four substrates - Canales-Gutiérrez, Angel (2021)
The aim of this study was to determine the growth and number of cocoons produced by Eisenia foetida (red worm) in four substrates. The treatments (substrates) were corn (T1), pumpkin (T2), sweet potato (T3) and potato (T4) in 1.5 kg of agricultural soil, 150 g of alpaca manure and 25 units of medium-size rocks. In total, 15 adult red worms were used per treatment, placed in wooden boxes and monitored for 40 days. The size and number of worms were measured, as well as the cocoons count. The length of the worms was similar for the treatments with corn (5.5 cm), potato (5.5 cm) and pumpkin (5.2 cm), but shorter in the treatment with sweet potato (4.0 cm; p=0.0045). On the other hand, there was no significant difference in the number of cocoons between treatments.